2008
DOI: 10.1007/s10620-008-0371-2
|View full text |Cite
|
Sign up to set email alerts
|

Serum Levels of Keratin-18 Fragments [Tissue Polypeptide-Specific Antigen (TPS)] Are Correlated with Hepatocyte Apoptosis in Alcoholic Hepatitis

Abstract: Apoptosis is a major feature in alcoholic hepatitis. During apoptosis, the M30 neoepitope becomes exposed after keratin-18 cleavage. The tissue polypeptide-specific antigen (TPS) is a keratin-18 fragment that is routinely used as a tumor marker. Serum TPS levels are increased in patients with alcoholic hepatitis. The aim of this study was to investigate the possible relationship of TPS levels with hepatocyte apoptosis in alcoholic hepatitis. Thirty-one patients with alcoholic hepatitis and 22 with fatty liver … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…The same group showed that serum levels of total CK18 correlated with the apoptotic score in 53 patients (31 with alcoholic hepatitis and 22 with fatty liver) [19]. While these studies were done on a small group of patients, the circulating level of total CK18 was increased in alcoholics.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…The same group showed that serum levels of total CK18 correlated with the apoptotic score in 53 patients (31 with alcoholic hepatitis and 22 with fatty liver) [19]. While these studies were done on a small group of patients, the circulating level of total CK18 was increased in alcoholics.…”
Section: Discussionmentioning
confidence: 95%
“…The serum levels of total CK18 in heavy drinkers (n = 15) were higher than those of healthy controls (n = 10), and even tended to be higher than those of patients with biopsy-proven malignancy of epithelial origin (n = 22) including adenocarcinoma of a variety of origins, small lung carcinoma, hypernephroma and epidermoid easophageal carcinoma [22]. The same group showed that serum levels of total CK18 correlated with the apoptotic score in 53 patients (31 with alcoholic hepatitis and 22 with fatty liver) [19]. More recently, it has been reported that serum levels of CK-18 fragment in patients with alcoholic hepatitis (n = 50) were higher than those of healthy controls (n = 50) and heavy drinkers (n = 50), and even tended to be higher than those of patients with malignancy (n = 50) [21].…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…For example, during apoptosis K18 is cleaved into small fragments by caspases. As a suitable indicative of hepatocytic apoptosis in vivo , one of the K18 proteolytic fragments, termed tissue polypeptide-specific antigens (TPS), can be readily detected in the plasmas of patients suffering from alcoholic hepatitis [4], nonalcoholic steatohepatitis[5,6], chronic cholecystitis [7] and chronic hepatitis B (CHB) [8]. In addition to scaffolding function, keratin filaments form complex signaling platforms and interact with kinases, adaptors and apoptotic proteins.…”
Section: Introductionmentioning
confidence: 99%
“…CK-18 is not an exclusively validated biomarker for AH but is a direct marker of hepatocyte apoptosis and, as such, probably should not be considered a diagnostic tool. (2) High levels of CK-18 has been most validated in patients with nonalcoholic steatohepatitis (versus simple steatosis) (3) and toxinassociated steatohepatitis. (4) Obese alcoholics with AH could have components of nonalcoholic steatohepatitis and AH working in tandem.…”
Section: To the Editormentioning
confidence: 99%